Evidence for the presence of activated CD4 T cells with naive phenotype in the peripheral blood of patients with rheumatoid arthritis. - Maurer, D (1992)
We have investigated whether T cell activation in rheumatoid arthritis (RA) preferentially engages distinct T cell subpopulations in the peripheral blood (PB) and in the synovial fluid. We found that CD25 expression was enhanced among PB CD4 T cells of RA patients as compared with CD4 cells of patients with reactive arthritis, degenerative joint disease or of healthy controls. Within the CD4 T lymphocytes subset we found that the CD45RO- (naive) cells selectively in RA displayed higher levels of CD25 protein and of interferon-gamma mRNA expression when compared with the respective subset of all other investigated groups. These results show that in the PB of RA, but not in the PB of the other arthropathies or healthy controls, CD45RO-CD4 T lymphocytes exist which display well-defined signs of activation.